Agrarian reform and social justice in the perspective of indonesian agrarian law: A systematic literature review - Ayang Fristia Maulana; Windi Maylawati; Asnawi Asnawi; Pringgo Angga Wijaya; Ujang Hibar (Institute Of computer Science (IOCS), 2026)
Agrarian reform is a crucial instrument in Indonesian agrarian law, aimed at reducing inequality in land ownership and achieving social justice as mandated by the constitution. Although the normative framework for agrarian reform has long been established through the Basic Agrarian Law and its various derivative policies, the realization of these objectives still faces fundamental challenges both at the regulatory and implementation levels. This study aims to systematically examine the development of scientific studies on agrarian reform and its relationship to the concept of social justice from the perspective of Indonesian agrarian law. The method used is a systematic literature review by analyzing journal articles, scientific books, laws and regulations, and relevant court decisions published within a specific period. The results of the study indicate that the agrarian law literature highlights a discrepancy between the normative objectives of agrarian reform and its implementation practices, particularly regarding the protection of land rights for smallholders and indigenous communities. Furthermore, the dominance of administrative and sectoral approaches in land management is considered not to fully reflect the principle of substantive social justice. This study concludes that achieving social justice through agrarian reform requires strengthening regulatory consistency, a legal approach oriented toward substantive justice, and an active role for the state in ensuring legal certainty and protection of land rights. This study is expected to provide a conceptual contribution to the development of agrarian law and serve as an academic and policy reference for implementing equitable agrarian reform.